“Influencia del momento del despuente en la produccion de tabaco (nicotiana tabacum), variedad habano pelo de oro, sector yacucatina- Juan Guerra” - Bardales Chujutalli, Marcial (2009)
With the aim of assessing the influence of the tipping point in the production of snuff (Nicotiana tabacum), variety cigar gold hair, was conducted this research work in the fields of ownership Natterman Hurme, located in the yacucatina district Juan Guerra, province and department of San Martín, about 28 km. the city of Tarapoto, 207 meters, south of latitude 06 º 38'02"west longitude and 76 º 12'05", with a maximum annual T 0 32 ° C, average annual precipitation of 200 mm and 1 a relativa humidity of 70-80%. The design used was a randomized complete block (DBCA), with 5 treatments and 4 replicates. The treatments were T1 (Despunte to bud), T2 (Despunte 25% of flowers open), T3 (Despunte 50% of flowers open), T 4 (Despunte 75% of flowers open) and T5 (no tipping). The results, the research work in times .of emergence is very important to obtain favorable in the production of snuff, and this shows the yield on the crop, where the T1 was a greater performance with a dry leaf 2 010.00 kg, net profit of S /. 3 140.00 new soles and the lowest yield was T5 with a 1 524.50 kg and a loss of S l. 3 357.00 nuevos soles per hectare, this whole performance is based on the activities being developed in a research paper using the timing of tipping.